If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 = 2 + 2p Solving -26 = 2 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -26 + -2p = 2 + 2p + -2p Combine like terms: 2p + -2p = 0 -26 + -2p = 2 + 0 -26 + -2p = 2 Add '26' to each side of the equation. -26 + 26 + -2p = 2 + 26 Combine like terms: -26 + 26 = 0 0 + -2p = 2 + 26 -2p = 2 + 26 Combine like terms: 2 + 26 = 28 -2p = 28 Divide each side by '-2'. p = -14 Simplifying p = -14
| 4x+7-8x-1= | | -4(8-5x)=72 | | 2/3=-8•x | | 4(x-6)/5=-4x | | 0.6x+2=0.2x | | 4x+7+8x-1= | | 23+x^2=2x | | P-12.6=24.57 | | 5+m*2= | | 4m/8=-4 | | 8(v-10)=40 | | 5x^2+5=75 | | -8(5+2v)+5(8v-6)=4v+3+v+3 | | 2x+8+22x=-2 | | 2/3=-8•× | | 21=r/18 | | 5/6=18/30 | | 21=#/18 | | 5+(m-2)= | | -5a=85 | | 0.4x-2=-0.6x | | 12/13=6k/5 | | 5t-23=-23+6t | | y-60=7493 | | (6n-10)/(n-4) | | 14-x=2+5 | | 0.4x-2=0.6x | | 0.4y+2x=1.2 | | 18x^2+5x-72=0 | | X+18=296 | | 6x-4y-3x+4=0 | | 5n-28=-64+9n |